2009
DOI: 10.1007/s11920-009-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, circadian rhythms, and the clock genes in bipolar disorder

Abstract: Sleep disturbances and dysregulation of circadian rhythms are core elements of bipolar disorder that might be involved in its pathogenesis. It has been proposed that patients with bipolar disorder have an abnormally shifted or arrhythmic circadian system and that the disturbance of circadian rhythms may be caused by an alteration in the circadian clock machinery. Chronotherapeutic strategies based on controlled exposures to environmental stimuli that act on biological rhythms have shown good efficacy in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 60 publications
3
34
0
1
Order By: Relevance
“…These variations apparently normalize with improved patient's clinical status (Dallaspezia and Benedetti 2009). …”
Section: The Influence Of Circadian Rhythms Disturbances On Bipolar Dmentioning
confidence: 95%
See 2 more Smart Citations
“…These variations apparently normalize with improved patient's clinical status (Dallaspezia and Benedetti 2009). …”
Section: The Influence Of Circadian Rhythms Disturbances On Bipolar Dmentioning
confidence: 95%
“…On the other hand, a study compared unipolar depression with BD and concluded that the latter had significantly lower levels and later onset of melatonin secretion (Robillard, Naismith et al 2013). In euthymic patients, there is a delayed melatonin's peak (Dallaspezia and Benedetti 2009).…”
Section: The Influence Of Circadian Rhythms Disturbances On Bipolar Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this association between 3111 T/C SNP and the bipolar disorder was not been replicated in an independent study (Nievergelt et al, 2006). In addition to the CLOCK gene, polymorphisms in other genes in the circadian clock system, such as PER3 , ARNTL , TIMELESS , ARNTL2 , DBP , VIP , and NR1D1 have been associated with the bipolar disorder (Mansour et al, 2006; Nievergelt et al, 2006; Benedetti et al, 2008; Shi et al, 2008; Soria et al, 2010) (for a review see (Dallaspezia and Benedetti, 2009)). However, polymorphisms in ARNTL , CLOCK , PER2 , PER3 were not shown be associated with the lithium therapy response (McCarthy et al, 2011) (Table 4).…”
Section: Circadian Regulation and Lithiummentioning
confidence: 99%
“…From these considerations, the literature reports a relationship between biological rhythm disturbances and treatment and the onset, maintenance and remission of bipolar episodes [3]. There is also evidence about the relevance of dys-regulation of hormones and neurotransmitters that command biological rhythms in bipolar disorders [4-8]. Physiological and behavioral timekeeping processes are frequently found abnormal in bipolar disorders, thus a vulnerability to alterations in biological rhythms may play a certain role in the course of the disease [9].…”
Section: Introductionmentioning
confidence: 99%